2017
DOI: 10.1371/journal.pone.0176885
|View full text |Cite
|
Sign up to set email alerts
|

Natural disasters and indicators of social cohesion

Abstract: Do adversarial environmental conditions create social cohesion? We provide new answers to this question by exploiting spatial and temporal variation in exposure to earthquakes across Chile. Using a variety of methods and controlling for a number of socio-economic variables, we find that exposure to earthquakes has a positive effect on several indicators of social cohesion. Social cohesion increases after a big earthquake and slowly erodes in periods where environmental conditions are less adverse. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
59
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 39 publications
8
59
1
Order By: Relevance
“…Other emerging evidence exploring the effects of post-election violence (Becchetti, Conzo, and Romeo 2014), and earthquake and tsunami damage (Caló-Blanco, et al 2015;Cassar, Healy, and Von Kessler 2011;Rao et al 2011) also mimics the main finding of this paper, namely that survival threats tend to enhance local cooperation. We expect that work in these areas will yield new insights about what psychological, economic and social mechanisms could lead those who experience violence to shift to more cooperative behavior.…”
supporting
confidence: 80%
“…Other emerging evidence exploring the effects of post-election violence (Becchetti, Conzo, and Romeo 2014), and earthquake and tsunami damage (Caló-Blanco, et al 2015;Cassar, Healy, and Von Kessler 2011;Rao et al 2011) also mimics the main finding of this paper, namely that survival threats tend to enhance local cooperation. We expect that work in these areas will yield new insights about what psychological, economic and social mechanisms could lead those who experience violence to shift to more cooperative behavior.…”
supporting
confidence: 80%
“…Unlike violence initiated by humans, natural disasters may leave community trust intact or bolster cooperation. In some settings, natural disasters are associated with reductions in violent crime [29][30][31], increases in family functioning [32,33], and prosocial behavior in communities and families [34][35][36]. One such study on communities affected by Hurricane Andrew found that one-third of respondents reported less stress with their neighbors than before the disaster, and 90% felt that the sense of sharing had been high in the neighborhood immediately after the hurricane and one year later [37].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to examine the factors that influence levels of social trust and conflicts in communities facing hardships after a natural disaster. Although it is hard to quantify the effects of natural disasters on levels of social trust and conflict separately, we can observe the net effects of natural disasters on social trust [20].…”
Section: Introductionmentioning
confidence: 99%